High magnetostriction and coupling coefficient for sintered cobalt ferrite derived from superparamagnetic nanoparticles - Mohaideen, Kamal Khaja; Joy, Pattayil Alias (Applied Physics Letters, 2012)
High magnetostriction (lambda) and coupling coefficient (d lambda/dH) of 315 ppm and 1.97 x 10(-9) A(-1) m, respectively, are obtained at room temperature for sintered cobalt ferrite derived from nanocrystalline powders. Also, the powder was compacted at a low pressure of 8 MPa and sintered for a short duration of 10 min at 1450 degrees C. Magnetic annealing at 300 degrees C in a field of 0.5 T for 30 min further enhanced the magnetostriction coefficient to 345 ppm with a higher coupling coefficient 2.12 x 10(-9) A(-1)m. The magnetic field above which maximum magnetostriction is observed is reduced by almost half after magnetic annealing. (C) 2012 American Institute of Physics. [http://dx.doi.org/10.1063/1.4745922]